Recent advances in marine ornamental breeding and seed production at Vizhinjam Regional Centre of CMFRI India - Anil, M. K.; Rohini Krishna, M. V.; Gomathi, P.; Surya, S.; Gop, Ambarish P.; Santhosh, B.; Siju, R.; Anand, V.; Krishnapriya, P. M.; Shalini, O.; Raju, B.; Madhu, K.; et al. (Frontiers in Marine Science, 2022)
The marine ornamental fish trading industry is an ever-expanding one, as indicated by its bolstering statistics, which amount to about US 300 million. Although the trade is booming, the natural habitats that foster these fishes, such as coral reefs, are steadily declining. One of the reasons for this is the overdependency of the industry on wild-caught fishes. To surpass this, the Central Marine Fisheries Research Institute (CMFRI) has developed hatchery technology for breeding marine ornamental fishes such as seahorses, clownfishes, damsels, and serranids. It began with the breeding of Hippocampus kuda. This progressed to breeding clownfishes such as Amphiprion chrysogaster, A. ocellaris, A. nigripes, A. peridarion, and A. ephippium and Premnas biaculeatus. Damsel fishes that were bred successfully include Chrysiptera cyanea, C. hemicyanea Neopomacentrus cyanomos, N. nemurus, and Dascyllus carneus. The recirculating aquaculture system (RAS) designed in the Vizhinjam Regional Centre of CMFRI is being used for broodstock development of serranids, tangs, squirrel fishes, and soldier fishes. A standard method was developed for captive breeding and hatchery rearing of anthias Pseudanthias marcia and P. squamipinnis in an advanced indigenous RAS system. The present article provides a bird’s eye view of the important research work done in India concerning marine ornamental fish breeding and reviews important breeding work carried out at Vizhinjam Regional Centre of CMFRI.